IMPLEMENTASI SISTEM INFORMASI MANAJEMEN RAPOR SISWA BERBASIS WEBSITE DENGAN MENGGUNAKAN AGILE METHOD (STUDI KASUS: SMPS ISLAM LADUNI) - Azmi Yaumi Arafah Rifa Putri; Farida Nurlaila (LPPM Politeknik Pratama Kendal, 2026)
The development of information technology has encouraged educational institutions to adopt digital systems to improve efficiency and transparency, one of which is through the implementation of a website-based student report card management information system. This is not only based on global trends, but also on the urgency of improving the quality of education in Indonesia. This study aims to facilitate SMPS Islam Laduni in managing student report cards, improving efficiency with easily accessible centralised data, while also providing a comprehensive academic management system with attendance and student ranking features. The Agile method with a qualitative approach in the form of observation, interviews, and literature studies was chosen to address the complex dynamics of school needs. As a result, there has been an improvement in the quality of the school's system through a centralised and flexible system. The report card management information system has succeeded in simplifying the report card management process, ensuring that report card data for each academic year is neatly structured and transparent. Based on the reliability test results, a score of 0.996 was obtained, which is in the very high category and is considered reliable. The test case results also show that the system is stable and meets the school's needs.